Damage Control for Thoracic Trauma. Issue 9 (September 2014) - Mackowski, Michael J.; Barnett, Rebecca E.; Harbrecht, Brian G.; Miller, Keith R.; Franklin, Glen A.; Smith, Jason W.; Richardson, J. D.; Benns, Matthew V.
Damage control surgery involves an abbreviated operation followed by resuscitation with planned re-exploration. Damage control techniques can be used in thoracic trauma but has been infrequently reported. Our goal is to describe our experience with the use of damage control techniques in treating thoracic trauma. A retrospective analysis of all patients undergoing damage control thoracic surgery related to trauma from January 1, 2010, to January 1, 2013, at University of Louisville Hospital, a Level I trauma center. Variables studied included injury characteristics, Injury Severity Score, surgery performed, duration of packing, length of stay (LOS), ventilator days, transfusion requirements, complications, and mortality. Twenty-five patients underwent damage control surgery in the chest with packing, temporary closure, and planned re-exploration after stabilization. Seventeen patients underwent anterolateral thoracotomy, and eight patients underwent sternotomy. The mean LOS and duration of temporary packing was 20.6 and 1.4 days in the thoracotomy group, respectively, and 19.5 and 1 day in the sternotomy group, respectively. The overall mortality rate was 40 per cent, 35 per cent in the thoracotomy group and 50 per cent in the sternotomy group. Like in severe abdominal trauma, damage control techniques can be used in the management of severe thoracic injuries with acceptable results.